Psoriasis severity in moderate to severe psoriatic Greek patients routinely treated with systemic treatment: a cross-sectional and retrospective chart review study (CRYSTAL-Greece) - Dimitrios Rigopoulos; J. Katsantonis; O. Neofotistou; V. Chasapi; E. Lazaridou; A. V. Roussaki-Schulze; M. Papakonstantis; C. Angelakopoulos; P. Rigatos; P. Aronis; C. Zeglinas; A. Kyriakakis; et al. (Journal of Dermatological Treatment)
Objective To characterize the systemic treatment patterns and current state of moderate-to-severe psoriasis patients in real-world settings in Greece.Methods CRYSTAL-Greece was a multicenter, cross-sectional and retrospective chart review study assessing Psoriasis Area and Index (PASI), Dermatology Life Quality Index (DLQI) and EuroQol-5-Dimensions 5-Levels (EQ-5D-5L). Eligible patients were consented adults (18–75 years old) on continuous treatment with any approved systemic therapy regimen for ≥24 weeks.Results 280 eligible patients were enrolled between 07APR2020 and 30NOV2020. Current treatment at the study visit was biologic monotherapy in 78.2% of patients, non-biologic monotherapy in 16.1%, and conventional systemic + biologic in 5.7%. Median absolute PASI score was 1.8; of patients, 36.8%/64.6%/83.9% had PASI ≤ 1/≤3/≤5. Rates of absolute PASI > 5 were 13.7% and 28.9% in the biologic and non-biologic monotherapy subgroups, respectively. Median DLQI score was 2.0, with 18.9% of patients having DLQI > 5 (16.0% and 26.7% in the biologic and non-biologic monotherapy subgroups, respectively). The correlation between DLQI and absolute PASI was low positive (Spearman rho = 0.432; p < 0.001). Most affected EQ-5D-5L dimensions were anxiety/depression (58.6%) and pain/discomfort (28.6%).Conclusion A considerable proportion of patients still do not achieve complete or almost complete skin clearance, while one fifth of the population experience at least moderate impairment of quality of life.